The effect of corporate income tax of agricultural companies on national budget? The case of the Slovak Republic - Juraj Chebeň; Renáta Krajčírová; Alexandra Ferenczi Vaňová; Michal Munk (Amfiteatru Economic Journal, 2021)
Corporate income tax significantly affects the overall amount of government tax revenue. In spite of the attention being paid to many macroeconomic indicators (e.g. GDP, inflation, unemployment rate, etc.) influencing the total amount of tax revenues influence, we can hardly find empirical research focused on the microeconomic view where the data is based on of the individual financial statements and tax returns of companies. Although the study is very practical, it assesses the extent of the mutual co-dependence between the corporate income tax and assorted variables via non-parametric correlation. Moreover, it presents the impact of the corporate income tax on the national tax revenue of the Slovak Republic within the sample of evaluated taxpayers operating in agriculture, forestry and fishing in 2011-2015 from SK NACE Rev. 2 section "A" category of companies as legal entities - Agriculture, forestry and fishing in 2011-2015. The study theoretically contributes to microeconomic-based view grounded on the adequate data of the legal entities, which were obtained from the corporate income tax returns provided by the Slovak Republic's Financial Directorate. The authors found out a significant rate of dependency between selected evaluated variables in all groups in the reviewed period. This dependency, especially between total income and tax base, as well as between total income and corporate income tax, is an essential part of the accounting result determined in the double-entry bookkeeping. The reliance is also the basis for the income tax base calculation from which the adjusted tax base is declared, and subsequently the corporate income tax is calculated. Research results tell the corporate income tax revenue of our sample makes up for, largely, 1.6% of the total tax revenue flowing to the Slovak national budget. Therefore, a set of recommendations was put forth in order to strive for a maximization of these tax revenues within the agricultural sector.
Keywords: H25; H61; H71; K34; 330; tax revenues; corporate income tax; corporate income tax rate; accounting result; income tax base